2016
DOI: 10.1186/s12891-016-1140-6
|View full text |Cite
|
Sign up to set email alerts
|

Scoliosis epidemiology is not similar all over the world: a study from a scoliosis school screening on Chongming Island (China)

Abstract: BackgroundSchool scoliosis screening has been carried out around the world. The screen program has never been performed on Chongming Island, the third largest island in China and characterized less population exchange with the rest of China. This study was designed to examine scoliotic parameters in children from Chongming Island and determine whether the parameters differed from those of the published data.MethodsA total of 6824 children (3477 boys and 3347 girls) aged from 6 to 17 were recruited. The screen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 38 publications
5
35
0
4
Order By: Relevance
“…For scoliosis examination a scoliometer, an effective and commonly used device for screening of scoliosis in the forward bending position (in which the person bends forward and the palms are pressed together between the knees), was used and the deviation was considered when it was ˃5 positive degrees [6,29]. Coelho et al indicated a maximum sensitivity of 87% and a specificity of 90% at the Cobb angle of 10° [19].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For scoliosis examination a scoliometer, an effective and commonly used device for screening of scoliosis in the forward bending position (in which the person bends forward and the palms are pressed together between the knees), was used and the deviation was considered when it was ˃5 positive degrees [6,29]. Coelho et al indicated a maximum sensitivity of 87% and a specificity of 90% at the Cobb angle of 10° [19].…”
Section: Methodsmentioning
confidence: 99%
“…One of the detectable disorders during school screening is scoliosis. In adolescents, its most common type is idiopathic scoliosis (80-90% of all cases of scoliosis), which can progress in the absence of treatment during the rapid growth phase of puberty, leading to significant abnormalities including pulmonary dysfunctions, reduced quality of life (QOL), heart failure, mental and psychological problems, back pain, and limitation in physical and motor activities [6,15,32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the 10°cut off suggested by the SRS, the prevalence still ranges widely throughout the world. In schoolchildren between the ages 6-17 years it ranges approximately between 0.13-2.52 %genetic differences are likely an explanation [21]. In the US, the prevalence for adults between 25-74 years is 8.3 % overall, with higher rates in the elderly and for women in general [22].…”
Section: Epidemiologymentioning
confidence: 99%
“…Scoliosis is a three-dimensional deformity with lateral curvature, sagittal hypokyphosis, and axial rotation of the spine. Adolescent idiopathic scoliosis (AIS) with a Cobb angle greater than 10 degrees occurs in the general population with a frequency ranging from 2% to 5% during growth, and the origin of the disease is unknown [ 1 4 ]. It has been highlighted that impairment of esthetic appearance of a patient’s body is significantly related to the patient’s negative image and self-respect, and the disease may cause reduced bone strength and balance disorder, among other effects [ 5 – 7 ].…”
Section: Introductionmentioning
confidence: 99%